Euro-Par 2010 - Parallel Processing 16th International Euro-Par Conference, Ischia, Italy, August 31 - September 3, 2010, Proceedings, Part I - D$1 (BAmbra, Pasqua.s; Guarracino, Mario; Talia, Domenico; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book constitutes the refereed proceedings of the 16th International Euro-Par Conference held in Ischia, Italy, in August/September 2010. The 90 revised full papers presented were carefully reviewed and selected from 256 submissions. The papers are organized in topical sections on support tools and environments; performance prediction and evaluation; scheduling and load-balancing; high performance architectures and compilers; parallel and distributed data management; grid, cluster and cloud computing; peer to peer computing; distributed systems and algorithms; parallel and distributed programming; parallel numerical algorithms; multicore and manycore programming; theory and algorithms for parallel computation; high performance networks; and mobile and ubiquitous computing.
Topic 1: Support Tools and Environments -- Distributed Systems and Algorithms -- Starsscheck: A Tool to Find Errors in Task-Based Parallel Programs -- Automated Tuning in Parallel Sorting on Multi-core Architectures -- Estimating and Exploiting Potential Parallelism by Source-Level Dependence Profiling -- Source-to-Source Optimization of CUDA C for GPU Accelerated Cardiac Cell Modeling -- Efficient Graph Partitioning Algorithms for Collaborative Grid Workflow Developer Environments -- Profile-Driven Selective Program Loading -- Characterizing the Impact of Using Spare-Cores on Application Performance -- Topic 2: Performance Prediction and Evaluation -- Performance Prediction and Evaluation -- A Model for Space-Correlated Failures in Large-Scale Distributed Systems -- Architecture Exploration for Efficient Data Transfer and Storage in Data-Parallel Applications -- jitSim: A Simulator for Predicting Scalability of Parallel Applications in Presence of OS Jitter -- pCFS vs. PVFS: Comparing a Highly-Available Symmetrical Parallel Cluster File System with an Asymmetrical Parallel File System -- Comparing Scalability Prediction Strategies on an SMP of CMPs -- Topic 3: Scheduling and Load-Balancing -- Scheduling and Load Balancing -- A Fast 5/2-Approximation Algorithm for Hierarchical Scheduling -- Non-clairvoyant Scheduling of Multiple Bag-of-Tasks Applications -- Extremal Optimization Approach Applied to Initial Mapping of Distributed Java Programs -- A Delay-Based Dynamic Load Balancing Method and Its Stability Analysis and Simulation -- Code Scheduling for Optimizing Parallelism and Data Locality -- Hierarchical Work-Stealing -- Optimum Diffusion for Load Balancing in Mesh Networks -- A Dynamic, Distributed, Hierarchical Load Balancing for HLA-Based Simulations on Large-Scale Environments -- Topic 4: High Performance Architectures and Compilers -- High Performance Architectures and Compilers -- Power-Efficient Spilling Techniques for Chip Multiprocessors -- Scalable Object-Aware Hardware Transactional Memory -- Efficient Address Mapping of Shared Cache for On-Chip Many-Core Architecture -- Thread Owned Block Cache: Managing Latency in Many-Core Architecture -- Extending the Cell SPE with Energy Efficient Branch Prediction -- Topic 5: Parallel and Distributed Data Management -- Parallel and Distributed Data Management -- Federated Enactment of Workflow Patterns -- A Distributed Approach to Detect Outliers in Very Large Data Sets -- Topic 6: Grid, Cluster and Cloud Computing -- Grid, Cluster and Cloud Computing -- Deployment of a Hierarchical Middleware -- Toward Real-Time, Many-Task Applications on Large Distributed Systems -- Scheduling Scientific Workflows to Meet Soft Deadlines in the Absence of Failure Models -- A GPGPU Transparent Virtualization Component for High Performance Computing Clouds -- What Is the Price of Simplicity? -- User-Centric, Heuristic Optimization of Service Composition in Clouds -- A Distributed Market Framework for Large-Scale Resource Sharing -- Using Network Information to Perform Meta-scheduling in Advance in Grids -- Topic 7: Peer to Peer Computing -- Peer-to-Peer Computing -- Overlay Management for Fully Distributed User-Based Collaborative Filtering -- Dynamic Publish/Subscribe to Meet Subscriber-Defined Delay and Bandwidth Constraints -- Combining Hilbert SFC and Bruijn Graphs for Searching Computing Markets in a P2P System -- Sampling Bias in BitTorrent Measurements -- A Formal Credit-Based Incentive Model for Sharing Computer Resources -- Topic 8: Distributed Systems and Algorithms -- Distributed Systems and Algorithms -- Improving Message Logging Protocols Scalability through Distributed Event Logging -- Value-Based Sequential Consistency for Set Objects in Dynamic Distributed Systems -- Robust Self-stabilizing Construction of Bounded Size Weight-Based Clusters -- Adaptive Conflict Unit Size for Distributed Optimistic Synchronization -- Frame Allocation Algorithms for Multi-threaded Network Cameras -- Scalable Distributed Simulation of Large Dense Crowds Using the Real-Time Framework (RTF) -- The x-Wait-Freedom Progress Condition.
Keywords: Computer science; Operating systems (Computers).; Computer system performance; Computer software; Electronic data processing; Computer Science; System Performance and Evaluation; Algorithm Analysis and Problem Complexity; Programming Techniques; Numeric Computing; Processor Architectures; Performance and Reliability